LEARNING ENVIRONMENT, SELF-EFFICACY, AND ATTITUDE IMPACT VOCATIONAL STUDENTS’ ENTREPRENEURIAL INTENTION? - Ari Saptono; Dedi Purwana E.S. (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2016)
This research aims to examine the impact of learning environment, self-efficacy, and an entrepreneurial attitude towards entrepreneurial intention of Vocational High School students in DKI Jakarta. This study applied survey method with causal approach. Sampling techniques is random cluster sampling stages whose result in sample of 310 respondents. Research data was collected by questionnaires and then analyzed with path analysis. Research results empirically show that: a) Students entrepreneurial intentions is affected directly and positively by the learning environment, self-efficacy, and an entrepreneurial attitude, b) the learning environment and self-efficacy are directly and positively impact on the entrepreneurial attitude, and c) the learning environment is directly and positively impact on self-efficacy. The results of the study conclude that with conducive learning environment, high self-efficacy and more positive entrepreneurial attitude will increase the entrepreneurial intention of Vocational High School students.